EDUCATIONAL AUTONOMY OF THE FUTURE TEACHER AS A NEW QUALITY OF THE PROFESSIONAL TRAINING - Drobotenko Ju. B.; Duka N. A.; Kurdumanova O. I.; Chekaleva N. V.; Sharov A. S.; Stefan Dyrka (Scientific Journal of Pedagogy and Economics, 2019)
The article considers the problems and ways of formation of educational independence of the future teacher, as abilities to consciously organize their own educational and cognitive activities on the basis of their capabilities, needs and interests. The main contexts of changes in the training of future teachers in this aspect are defined by the Federal State Educational Standard of Higher Education, the professional standard “Teacher” and the requirements of the modern paradigm of vocational education, in which the student takes the position of an equidistant, self-governing subject of educational activity. The article shows, how these circumstances affect the nature of the student’s educational and cognitive activities. The presentation of educational autonomy as a new quality of vocational training reveals a meaningful development of the concept of competence in vocational education. The description of educational autonomy through such components as the result of internal motivation, the activity of the future specialist in the pursuit of knowledge and self-education, including the skills of targeting, planning and control in educational and cognitive activities, allows to investigate this phenomenon empirical. Empirical data of study of educational autonomy of future teachers was presented.